Risk of opioid abuse and educational technologies in patients with chronic pain: a scope review protocol (Research, Society and Development, 2023)
Objective: To identify in the literature the risks of abuse of opioids and the use of educational technologies in the form of applications in patients with chronic pain. Method: Scope review to answer the question “What are the risks of abusive use of opioids in patients with chronic pain? Na what educational technologies are used in patients with chronic pain using opioids?” The search will be carried out in the MEDLINE, LILACS, SCOPUS, EMBASE, Web of Science and Cinahl databases and gray literature. The identified studies will be imported into a reference manager and duplicates will be removed. Titles and abstracts will be read and analyzed, meeting the inclusion criteria of this review, by two independent reviewers. Studies selected by title and abstract will be read in full and evaluated by two reviewers. Those Who meet the inclusion criteria after reading in full will be included in the review for data extraction. If there is disagreement between the reviewers, a third reviewer will be contacted. Extracted data will be presented in a diagram or tabular form in a manner that aligns with the objective of this scoping review, and a narrative summary will be provided.